Chinese version of Yoon Critical Thinking Disposition Instrument: validation using classical test theory and Rasch analysis - Mio Leng Au; Yue Yi Li; Lai Kun Tong; Si Chen Wang; Wai I Ng (BMC Nursing, 2023)
Abstract Background Despite the availability of a wide range of critical thinking instruments, there was no original design for nurses that has been translated into Chinese. However, only instruments designed specifically for the nursing discipline would be reliable. This study aimed to translate, culturally adapt, and validate the Yoon Critical Thinking Disposition Instrument in the Chinese context. Methods A four-step translation process was implemented according to Word Health Organization guidelines, which included forward translation, expert panel review, backward translation, and pre-testing. Experts and nursing students participated in testing the validity and reliability of the Chinese version. Results The translation of the instrument went smoothly. According to a confirmatory factor analysis, there was an acceptable fit for the seven-factor model. Content validity indices ranged from 0.6 to 1 at item level, and 0.94 at scale level. In addition, there was extremely high internal consistency and test-retest reliability in the translated instrument. There was a good fit for the items with both person and item reliabilities greater than 0.6 and a separation index of 2.19, respectively. The item location was identified from the wright map as not covering person ability, but the scale did not have a gender-related differential item functioning. Conclusions In this study, a critical thinking disposition instrument for nursing students was translated into Chinese for the first time. This translated instrument is a reliable tool with satisfactory validity and reliability. It could provide opportunities for building a cross-cultural understanding of critical thinking disposition.